Comparison of foot segment kinematics according to pedaling power output level in female cyclists - Gil, H.-J.; Yoon, S. (Korean Journal of Sport Biomechanics, 2025)
Objective: The purpose of this study was to compare the kinematic characteristics of the foot segment between high-power and low-power pedaling groups in female cyclists, using functional biomechanical event points. Method: The study participants were 12 female road cyclists. They were divided into a high-power group (HPG, n=6; age: 29.6 ± 5.7 yrs., height: 163.8 ± 6.6 cm, body weight: 58.1 ± 4.8 kg, power output: 261.3 ± 31.8 W, power-to-weight ratio: 4.5 ± 0.5 W/kg) and a low-power group (LPG, n=6; age: 33.3 ± 12.1 yrs., height: 162.6 ± 7.4 cm, body weight: 56.1 ± 5.3 kg, power output: 167.5 ± 26.3 W, power-to-weight ratio: 3.0 ± 0.4 W/kg) according to the 5-minute functional threshold power output (=200 W or <200 W). Three-dimensional kinematic data were collected using a nine-camera motion capture system (100 Hz) during pedaling on a stationary smart trainer. The pedal cycle was segmented based on functional event points: E1 (30°), E2 (150°), E3 (210°), and E4 (330°). Foot segment angle (FSA), angular velocity (FSAV), and angular acceleration (FSAA) were analyzed at each event point and within each phase (P1-P4). Results: First, no significant differences were observed between groups in FSA, range of motion, or angular velocity at any event point or phase. Second, the maximum angular acceleration during the main propulsive phase (P1: 30-150°) was significantly greater in HPG than in LPG (p<.05, d=1.808). Third, the angular acceleration at E2 (150°) was significantly greater in HPG than in LPG (p<.05, d=1.321). Both variables showed large effect sizes. Conclusion: The kinematic distinction between high-power and low-power pedaling in female cyclists was more evident in foot segment angular acceleration than in angular position or velocity. These findings suggest that training interventions targeting rapid foot segment acceleration during the early propulsive phase may enhance pedaling efficiency in recreational cyclists.